2006
DOI: 10.1002/pmic.200500927
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory effect of the minor Streptomyces lividans type I signal peptidases on the SipY major signal peptidase deficiency as determined by extracellular proteome analysis

Abstract: The developmentally complex bacterium Streptomyces lividans has the ability to produce and secrete a significant amount of protein and possesses four different type I signal peptidase genes (sipW, sipX, sipY and sipZ) that are unusually clustered in its chromosome. 2-DE and subsequent MS of extracellular proteins showed that proteins with typical export signals for type I and type II signal peptidases are the main components of the S. lividans secretome. Secretion of extracellular proteins is severely reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Other actinobacteria have been reported to secrete substantially more proteins. Roughly 50% of the extracellular proteins of Corynebacterium diphtheriae had signal peptides, and 75% of supernatant proteins had signal peptides in Streptomyces lividans (10,14). The low degree of protein secretion in Frankia could be related to the medium used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other actinobacteria have been reported to secrete substantially more proteins. Roughly 50% of the extracellular proteins of Corynebacterium diphtheriae had signal peptides, and 75% of supernatant proteins had signal peptides in Streptomyces lividans (10,14). The low degree of protein secretion in Frankia could be related to the medium used.…”
Section: Resultsmentioning
confidence: 99%
“…In minimal medium, exported proteins may not be produced; for example, Bacillus subtilis and Bacillus licheniformis secrete large amounts of protein when grown in rich medium (36). Conversely, in Streptomyces species grown in minimal medium, the lack of complex nutrients stimulates cells to secrete proteins in order to scavenge resources (10). Bioinformatics analysis of the three Frankia genomes predicted few degradative enzymes, so it is unlikely that the medium alone accounts for the minimal secretome in strain CcI3 (22).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a general role in cell surface events, over half of the proposed U regulon genes encode probable secreted proteins, lipoproteins, (16). d N-terminal signal peptide cleavage site predicted using the SignalP 3.0 server (15).…”
Section: Discussionmentioning
confidence: 99%
“…We have focused on defining the genetic targets and proteomic consequences of activity for U , given the dramatic effect that uncontrolled activity of this sigma factor has on halting the developmental progress of S. coelicolor. With direct evidence from GFP reporter studies and supporting evidence from proteomic studies, we propose TGA(A/G)C(A/G)(N [16][17] )CGTA as a provisional promoter consensus sequence for U -dependent genes and have used this sequence to identify likely U regulon members. This consensus sequence is entirely consistent with the results of a recent microarray study that identified a group of 18 genes, including sigU and 6 of the regulon members proposed here, as having similar expression profiles during growth of M600 S. coelicolor on a maltose-based solid medium (see reference 25, additional data file 6, QT cluster 11).…”
Section: Discussionmentioning
confidence: 99%
“…Upon complementation of the SipY mutant with each of the Sip proteins encoded in multicopy plasmids, the SipY mutant sporulation-delayed phenotype was repaired and the analysis of extracellular proteins indicated that the overall pattern of secretory proteins had recovered in all cases (Escutia et al 2006). The conclusion reached is that individual mutations in the different S. lividans sip genes, except for sipY, do not seem to exert a severe effect on protein secretion, as observed previously (Palacín et al 2002), due to the compensatory effects of the minor SPases.…”
Section: Type I Signal Peptidases In S Lividansmentioning
confidence: 98%